1986
DOI: 10.1073/pnas.83.17.6470
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the fibronectin receptor complex in cells transformed by oncogenes that encode tyrosine kinases.

Abstract: The fibronectin (FN) receptor in avian cells has been characterized previously as a complex of three membrane glycoproteins of about Mr 160,000, Mr 140,000, and Mr 120,000 (simply termed protein band 1, band 2, and band 3, respectively). Monoclonal antibodies to the band 3 protein of the complex prevent FN and laminin binding both in vivo and in vitro and enable the detection of the receptor proteins in the plasma membrane and in adhesion plaques. Association of the FN receptor proteins with the adhesion-plaqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
191
2
2

Year Published

1988
1988
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(202 citation statements)
references
References 49 publications
7
191
2
2
Order By: Relevance
“…Among these are paxillin, talin, subunits of the integrin receptor, the focal adhesion kinase p125 FAK and vinculin (Sefton et al, 1981;Hirst et al, 1986;Pasquale et al, 1986;Turner, 1991;Guan and Shalloway, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Among these are paxillin, talin, subunits of the integrin receptor, the focal adhesion kinase p125 FAK and vinculin (Sefton et al, 1981;Hirst et al, 1986;Pasquale et al, 1986;Turner, 1991;Guan and Shalloway, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The potential role of the FNR in neoplasia was suggested by the findings that the FNR is phosphorylated in v-src transformed cells (Hirst et al, 1986); that transforming agents affect the structure, function, and expression levels of the alpha5betal FNR (Plantefaber and Hynes, 1989;Symington et al, 1989); and that glycine-arginine-glycine-aspartate-serine (GRGDS) peptide or anti-beta1 antibodies can prevent pulmonary metastases of B16 melanoma cells (Humphries et al, 1986). Our interest in the potential role of the FNR in tumor metastasis prompted efforts to generate alpha5betal expression variants of established tumorigenic cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…This down-regulation in the level of phosphorylation could play a functional role in the phenotypic conversion of F9 to RA cells, especially if there were differential switching between the two integrins. Hirst et al (1986) also have shown that integrin phosphorylation occurs, raising the possibility that interactions with talin or other cytoplasmic proteins might be modulated by phosphorylation changes to affect function. If this model were correct in the present context, retinoic acid would lead to altered integrin expression on the cell surface but the importance of that alteration, phenotypically, would be the alteration of organization of integrins with the cytoskeleton, setting up a differential ability to form focal contacts.…”
Section: Discussionmentioning
confidence: 99%